1923’ten 2023’e Türkiye Ekonomisi - Uluğ, Eyüp Emre; Doğan, İbrahim; Somuncu, Ahmet; Ayvaz, Erkam Emin; Aslan, Alper; Oralhan, Burcu; Akagündüz, Halit Kerem; Himmetoğlu, Salih; Yılmaz, Şaban Fatih; Demirel, Neslihan; Şanlıoğlu, Ömer; Bulut, Yasin; et al. (2024)
-